Factors associated with health facility utilization during childbirth among 15 to 49-year-old women in Uganda: evidence from the Uganda demographic health survey 2016 - Quraish Sserwanja; David Mukunya; Milton W. Musaba; Joseph Kawuki; Freddy Eric Kitutu (BMC, 2021)
Abstract Background Almost all maternal deaths and related morbidities occur in low-income countries. Childbirth supervised by a skilled provider in a health facility is a key intervention to prevent maternal and perinatal morbidity and mortality. Our study aimed to establish the factors associated with health facility utilization during childbirth in Uganda. Methods We used the Uganda Demographic and Health Survey 2016 data of 10,152 women aged 15 to 49 years. The study focused on their most recent live birth in 5 years preceding the survey. We applied multistage stratified sampling to select study participants and we conducted multivariable logistic regression to establish the factors associated with health facility utilization during childbirth, using SPSS (version 25). Results The proportion of women who gave birth at a health facility was 76.6% (7780/10,152: (95% confidence interval, CI, 75.8-77.5). The odds of women aged 15-19 years giving birth at health facilities were twice as those of women aged 40 to 49 years (adjusted odds ratio, AOR = 2.29; 95% CI: 1.71-3.07). Residing in urban areas and attending antenatal care (ANC) were associated with health facility use. The odds of women in the northern region of Uganda using health facilities were three times of those of women in the central region (AOR = 3.13; 95% CI: 2.15-4.56). Women with tertiary education (AOR = 4.96; 95% CI: 2.71-9.11) and those in the richest wealth quintile (AOR = 4.55; 95% CI: 3.27-6.32) had higher odds of using a health facility during child birth as compared to those with no education and those in the poorest wealth quintile, respectively. Muslims, Baganda, women exposed to mass media and having no problem with distance to health facility had higher odds of utilizing health facilities during childbirth as compared to Catholic, non Baganda, women not exposed to mass media and those having challenges with distance to access healthcare. Conclusion Health facility utilization during childbirth was high and it was associated with decreasing age, increasing level of education and wealth index, urban residence, Northern region of Uganda, ANC attendance, exposure to mass media, tribe, religion and distance to the nearby health facility. We recommend that interventions to promote health facility childbirths in Uganda target the poor, less educated, and older women especially those residing in rural areas with less exposure to mass media.